PERAN KEPERCAYAAN DAN TEKNOLOGI INFORMASI TERHADAP KINERJA RANTAI PASOK : Studi Pada Usaha Mikro Kecil Dan Menengah Tempe di Banten - Lias Dita , Suryaputra; Mohammad, Mukhsin (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2023)
This research aims to analyze trust and information technology's influence on Tempe Micro, Small, and Medium Enterprises (MSMEs) supply chain performance in Banten Province. This research uses a quantitative approach. The population in this research is all Tempe MSMEs in Banten. The sample in this study was 64 tempe MSMEs located in 8 (eight) districts/cities. Sampling was taken using stratified random sampling, namely 8 (eight) respondents in each district/city. The data is primarily obtained through a questionnaire and then processed using the SmartPLS 4 tool. The research results show that trust and information technology has proven to influence the supply chain performance of tempeh MSMEs in Banten. High trust between business partners in the supply chain provides benefits in the form of better collaboration, effective communication, and more excellent reliability in meeting customer needs and demands. The use of sophisticated information technology allows MSMEs to speed up business processes, increase data accuracy, optimize coordination with business partners, and increase responsiveness to changes in market demand.